GAMBARAN DUKUNGAN KELUARGA DAN KUALITAS HIDUP ANAK KANKER DI YAYASAN PEDULI KANKER ANAK BALI - Utami, Kadek Cahya; Puspita, Luh Mira (Coping: Community of Publishing in Nursing, 2020)
Chemotherapy is one of the most effective therapies for patients with cancer. In addition to its therapeutic effects, chemotherapy can also have side effects on children with cancer. Chemotherapy and its side effects can have an impact on children with cancer, particularly those requiring repeated hospitalizations, who are left with bad experiences from the therapies. In light of this fact, the treatment certainly can have an impact on the children’s quality of life. One of the outstanding factors influencing the quality of life of children with cancer is family support. In this regard, the aim of the present study was to determine the description of family support and quality of life for children with cancer who receive chemotherapy. This study was a descriptive study with a cross-sectional design. The sample of the present study consisted of 30 children. The results showed that most of the respondents' parents were able to provide optimal family support (13.40), and most children with cancer who received chemotherapy had a good quality of life (74.63). This suggests that nursing services need to make efforts to maintain effective family support in order to improve the quality of life for children with cancer who receive chemotherapy. Keywords: children with cancer, family support, quality of life